The Effect of STEAM Integrated Project Based Learning on Students’ Critical Thinking on Static Fluids Concept - Simanjuntak, Mariati Purnama; Rajagukguk, Juniastel; Panjaitan, Dita Trisna; Siagian, Asister Fernando (Universitas Negeri Semarang, 2025)
This study aims to see the effect of project-based learning (PjBL) integrated with the STEAM approach (Science, Technology, Engineering, Arts, and Mathematics) on students' critical thinking skills on static fluid material in grade XI of high school. The research employed a quasi-experiment with a two-group pretest–posttest control group design. The sample consisted of two classes, namely class XI MIA 2 (experimental group) and class X MIA 1 (control group), which were selected using a simple random sampling technique, with each class consisting of 36 students. The research instrument used was an essay test designed to assess students' critical thinking skills. The data were analysed using a t-test to determine the differences between groups. Pretest results indicated comparable initial critical thinking abilities between the experimental and control groups. However, following the implementation of STEAM-integrated PjBL, the experimental group demonstrated a significant improvement in post-test scores compared to the control group. This improvement was reflected in a higher percentage increase in critical thinking skills, indicating the positive impact of the integrated approach. The effectiveness of this intervention was further supported by a high score on the relative effectiveness test, emphasizing its value in enhancing critical thinking skills. These findings suggest that active, interdisciplinary learning strategies can effectively enhance students' analytical and problem-solving abilities, better preparing students for real-world challenges through deeper engagement and creative thinking.